God’s Reign in the Psalms and the Kingdom of God - Firth, David G. (Tyndale bulletin, 2025)
Jesus’s use of the language of the Kingdom assumes that his audience was familiar with the concept. The most obvious place to seek a background for it is therefore in the Old Testament. Although the term itself is found only infrequently there, it does occur at a few points. By far the richest Old Testament source for understanding the Kingdom is the Book of Psalms because of its consistent emphasis on the theme of God as king. This motif comes to particular prominence in Book 4. Previous studies of this book have struggled to connect the language here to the Kingdom because of the dominance of form critical models, but newer canonical approaches allow us to understand more clearly how the language of God’s reign is here applied to the particular needs of the community addressed by that book. This is particularly important in Psalms 93, 97, and 99, which speak of YHWH’s reign. Although not explicitly cited in the New Testament, these psalms provide important background to the presentation of the Kingdom in the book of Revelation, which likewise uses the language of the Kingdom to provide hope for those who struggle. The good news of the Kingdom in Jesus’s proclamation is therefore not an abstract statement about God’s reign but a message that addressed the needs of the community who heard him.